The Timing of Breast Irradiation in Two‐Stage Expander/Implant Breast Reconstruction. Issue 3 (11th February 2016) - Yan, Chen; Fischer, John P.; Freedman, Gary M.; Basta, Marten N.; Kovach, Stephen J.; Serletti, Joseph M.; Lin, Lilie; Wu, Liza C.
Abstract: Certain patients who initiate expander/implant (E/I) reconstruction following mastectomy may require radiation therapy (XRT). XRT may be delivered during the tissue expander (TE) expansion process or after exchange for a permanent implant (PI). We studied a series of women treated with E/I reconstruction and XRT to determine whether there is a difference in complication rates between those who had XRT to the TE versus PI. All two‐stage E/I reconstructions at our institution from April 2005 to January 2013 were reviewed to identify patients who underwent XRT after TE placement. Our database was queried for reconstructive details, oncologic treatment, and complications. Statistical analyses were performed to establish significance of complication rate differences. Fifty‐two patients underwent XRT after TE placement, 42 of which had XRT to the TE and 11 of which had XRT to the PI. The major complication rates (complications requiring emergent reoperation/readmission) were 27% versus 0% (p = 0.05) for XRT to the TE versus XRT to the PI, but there were no significant differences in minor complication rates (outpatient complications). Specifically, the rates of Grade 3/4 capsular contracture were similar between the two groups, 27% for the XRT to the TE group and 36% for the XRT to the PI group. Radiation of the PI versus radiation of the TE did not result in significant differences in overall surgical complication rates but had fewer major complications and no implant failures. Other factors must also be considered, such as patient preference, risk of cancer reoccurrence, and cosmesis. It is essential for a patient to have a team of a plastic surgeon and radiation, surgical, and medical oncologists working together to achieve each patient's goals.